The importance of the employer brand on the labour market: case study from Czech Republic - Renata SKYPALOVA; Monika VENCOUROVA; Vendula HYNKOVA; Tomas JERABEK (Communications of International Proceedings, 2023)
The case study proposes a methodological procedure for building an employer brand applied to two real companies between 2016 and 2019. The process of creating an employer brand includes three phases: (1) knowledge – analysis of the current situation and setting SMART goals, (2) creation – design of a communication strategy and selection of appropriate communication tactics and (3) implementation – development of an action plan with detailed calculation and design of control tools. The paper focuses on ways in which marketing and HR departments should work together to develop a good employer brand. Other sub-issues include: Can the same method of employer branding methodology be implemented in industrial and service corporations? Are the same principles important both in a B2B company and in a company in the B2C market? The paper presents the results of a focus group survey and a questionnaire survey among employees of two selected companies. The results of the study show that through cooperation it is possible to formulate meaningful job offers, become a company attractive to employees, fulfill their needs and at the same time fulfill the company's strategic goals.
Keywords: Human Resource Management; Employer Brand; Czech Republic; Labor Market